Enxadas de açúcar : um estudo sobre economia e formação social na ficção de José Lins do Rêgo - Duarte, Mariana (My University, 2014)
The subject of this dissertation is the study of the social and the economic contributions of the Brazil’s Northern region based on an analysis of three novels from the Brazilian writer José Lins do Rêgo (1901-1957): Menino de Engenho (1932), Usina (1936) and Fogo Morto (1943). From the interdisciplinary dialogue between History and Literature, this research aims at identifying the contribution of the social studies and the fiction in the economic formation of regional types and the construction cultural identity of the Northern region. The structure of the present text is composed by three aspects, which are the main subject of each chapter of the dissertation: the economy, the society and the representations of history and literature in this social context. As a theoretical basis, we use the cultural studies, the approach between both fictional and historical discourses and the concept of region as a cultural construct, which will be formed both from literary and historiographic texts.
O tema da presente dissertação consiste no estudo da contribuição econômica e social nordestina a partir de três romances do escritor José Lins do Rêgo (1901-1957): Menino de Engenho (1932), Usina (1936) e Fogo Morto (1943). Partindo da perspectiva do diálogo interdisciplinar entre História e Literatura, essa análise visa à identificação da contribuição dos estudos sociais e da ficção na formação econômica, dos tipos regionais e na construção da identidade cultural nordestina. A estrutura do trabalho é composta por três aspectos, que constituem o assunto principal de cada capítulo da dissertação, a partir da sua verificação nas obras de José Lins do Rêgo: a economia, a sociedade e as representações da história e da literatura nesse contexto ficcional. Como base teórica serão utilizados os estudos culturais, as aproximações entre os discursos ficcionais e históricos, o conceito de região enquanto construção cultural que se formará a partir dos textos literários e também historiográficos.
Keywords: Rego, José Lins do; Literatura e história; Literatura e história; Civilização - História; Literatura brasileira